2022
DOI: 10.1016/j.jmig.2021.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical and Reproductive Outcomes between Adenomyomectomy and Myomectomy

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…We agree with other groups that adenomyosis should be part of the differential diagnosis in patients with infertility at the first consultation. While there may be benefits from surgical treatment of adenomyosis before IVF, resection may be incomplete in case of lack of capsule, and the risk of uterine rupture during pregnancy may be higher 26 . Therefore, surgery may not be recommended for patients with infertility without symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We agree with other groups that adenomyosis should be part of the differential diagnosis in patients with infertility at the first consultation. While there may be benefits from surgical treatment of adenomyosis before IVF, resection may be incomplete in case of lack of capsule, and the risk of uterine rupture during pregnancy may be higher 26 . Therefore, surgery may not be recommended for patients with infertility without symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…While there may be benefits from surgical treatment of adenomyosis before IVF, resection may be incomplete in case of lack of capsule, and the risk of uterine rupture during pregnancy may be higher. 26 Therefore, surgery may not be recommended for patients with infertility without symptoms. Furthermore, several studies demonstrated no difference in pregnancy outcomes between women with and those without US‐diagnosed adenomyosis undergoing long‐term downregulation ovarian stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These positive findings were echoed in a retrospective cohort comparing patients who underwent adenomyomectomy vs. myomectomy via laparoscopic or open approach, with a live birth rate of 46 vs. 71%, P = 0.076 [46]. In patients whose endometrial cavity was entered intra-operatively, hysteroscopy 3 months later revealed 35% with stage I intrauterine synechiae, treated with adhesiolysis [46]. A retrospective series of all 22 pregnancies after adenomyomectomy performed by a single surgeon from 2011 to 2019 found four placental abnormalities, one case of uterine rupture, and no hysterectomies [47].…”
Section: Treatment Of Adenomyosis For Patients With Infertilitymentioning
confidence: 93%
“…A recent systematic review suggested that pregnancy is likely safe after excisional procedures with low rates of uterine rupture (1/126, 0.8%) and a delivery rate of 81% [44]. These positive findings were echoed in a retrospective cohort comparing patients who underwent adenomyomectomy vs. myomectomy via laparoscopic or open approach, with a live birth rate of 46 vs. 71%, P = 0.076 [46]. In patients whose endometrial cavity was entered intra-operatively, hysteroscopy 3 months later revealed 35% with stage I intrauterine synechiae, treated with adhesiolysis [46].…”
Section: Treatment Of Adenomyosis For Patients With Infertilitymentioning
confidence: 99%